Metal–organic framework nanosheets for enhanced performance of organic photovoltaic cells. Issue 12 (13th March 2020) - Sasitharan, Kezia; Bossanyi, David G.; Vaenas, Naoum; Parnell, Andrew J.; Clark, Jenny; Iraqi, Ahmed; Lidzey, David G.; Foster, Jonathan A.
Abstract : Metal–organic framework nanosheets (MONs) are incorporated into the active layer of bulk heterojunction polymer–fullerene solar cells for the first time, resulting in an almost doubling of power conversion efficiency. Abstract : Metal–organic framework nanosheets (MONs) are an emerging class of two-dimensional materials whose diverse and readily tunable structures make them ideal for use in optoelectronic applications. Here, liquid exfoliation is used to synthesize ultrathin zinc-porphyrin based MONs with electronic and optical properties ideally suited for incorporation into a polythiophene–fullerene (P3HT–PCBM) organic solar cell. Remarkably, the addition of MONs to the photoactive layer of a photovoltaic device results in a power conversion efficiency of 5.2%, almost twice that for reference devices without nanosheets with a simultaneous improvement of J sc, V oc and FF. Our analysis indicates that the complimentary electronic, optical and structural properties of the MONs allows them to act as a surface to template the crystallization of P3HT leading to a doubling of the absorbance, a tenfold increase in hole mobility and reduced grain size. These results demonstrate the potential of MONs as a tunable class of two-dimensional materials for enhancing the performance of a broad range of organic solar cells and other electronic devices.